Analysis of the Efficiency of the RITM-200 Nuclear Power Installation Using Neutron-Physical and Thermo-Hydraulic Modeling for Autonomus Energy Systems - Asalkhon Z. Mirzayeva; Sherzod S. Djumanov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: in remote regions facing energy shortages, reliable autonomous energy sources are essential. Small modular reactors (SMRs) can provide continuous power supply with high safety standards and extended fuel cycles. Aim:to analyze the efficiency of the RITM-200 nuclear power installation using neutron-physical and thermo-hydraulic modeling for autonomous energy systems. Methods: the study applied neutron-physical modeling of the reactor core considering fuel composition, enrichment, and absorbers, as well as thermo-hydraulic calculations covering temperature regimes, heat transfer, and the Rankine cycle. Results: the use of silumin and erbium dioxide in the fuel composition significantly increases fuel burnup depth and fuel cycle duration, while enhancing operational safety. The calculations confirm the applicability of the installation for energy supply in hard-to-reach regions.